Spatial and temporal representation of earthquake data in Saudi Arabia for the period 1980 - 2018AD - Al-Amri, Afaf Rafi Abdullah (Journal of natural sciences, life and applied sciences, 2022)
The research presented an analysis of earthquake data in Saudi Arabia for the period between 1980-2018 AD, including geographical representation to reveal the data's dimensions and characteristics. The research results focused on the relationship between the frequency of earthquake occurrence near and far from urban areas. Emphasis was placed on the region in which the seismic data were strongest on the Richter scale during the time under study. The inductive and quantitative mathematical methods were used to analyze the data and represent the outputs, and the objective analytical method was used to interpret the results. The results were analyzed using spatial statistical analysis tools to obtain a geographical representation of the earthquake data, where the (Directional Distribution) tool was used to measure the direction of the data distribution, as well as the statistical analysis technique (Buffer) to determine the extent of the potential damage to urban areas around the earthquake area. The results of data analysis through cartographic representation showed that the northwestern and western regions of the Kingdom of Saudi Arabia are the most threatening to urban areas close to earthquake sites. This study recommends intensifying research efforts on seismic event data from the perspective of managing natural hazard data and its impact on neighboring urban areas.
Keywords: spatial representation; temporal representation; seismic data management; geographic information systems; spatial analysis